ASSISTANCE IN READING AND WRITING AL-QURAN AT PRIMA TPA KAMPUNG BARU PCIM MALAYSIA - Ibrahim Ibrahim; Ilham Zitri; Inka Nusamuda Pratama (JOURNAL OF PROGRESSIVE INNOVATION LIBRARY SERVICE, 2024)
This service aims to provide assistance in reading and writing the Koran to TPA Prima participants in Kampung Baru, PCIM Malaysia. The mentoring method is carried out through structured and interactive learning sessions. The research was conducted involving participatory observation and evaluation of participant learning outcomes. The results of the service showed a significant increase in the ability to read and write the Koran among TPA Prima participants. Directed learning sessions supported by individual mentoring have helped participants to improve their pronunciation and understand the meaning of the Al-Quran text better. Apart from that, participants also experienced an increase in their ability to write Arabic letters and Al-Quran words correctly. This service makes a positive contribution in improving Al-Quran reading and writing skills among TPA Prima participants. The practical implication is the need for continued mentoring programs that are sustainable and supported by adequate resources to strengthen TPA Prima participants' understanding and skills of the Al-Quran in the future.